Valentino’s syndrome – a systematic review of a life-threatening mimic of acute appendicitis - Salati, Sajad Ahmad; AlSalamah, Yasir Ahmed; AlSulaim, Lamees Sulaiman (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Valentino’s syndrome is an atypical but potentially lethal presentation of a perforated peptic ulcer. It closely mimics appendicitis. Literature about this disorder is sparse due to its rarity. Hence, this article was compiled to gain an understanding of this disorder. This article was composed to review the profiles of patients with Valentino’s syndrome reported in the recent literature. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A systematic literature search was conducted through electronic databases, including PubMed, ResearchGate, and Scopus, using the key words and terms “Valentino’s syndrome,” “perforated duodenal ulcer simulating acute appendicitis,” and “perforated peptic ulcer mimicking acute appendicitis.” Only English literature was considered for inclusion in this study, and the time frame was fixed between 2012 and 2023. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Twenty-seven cases from both genders, ranging in age from 7 to 76 years, were included in the review. In 20 cases, the diagnosis was made at laparotomy for a presumed diagnosis of acute appendicitis. Six cases had undergone appendectomy as their first surgical operation, but their condition had worsened postoperatively and had undergone re-exploration at a delay of 3 to 10 days (mean 6±2.86 days; mode 3 days). One patient required a third abdominal exploration. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Valentino’s syndrome has a very high rate of misdiagnosis. There is a need to increase awareness of this disorder among healthcare professionals so that it might be considered a differential diagnosis while a patient is being evaluated for acute abdomen.